2019
DOI: 10.1101/2019.12.20.884288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebellar dopamine D2 receptors regulate preference for social novelty

Abstract: The cerebellum, a primary center involved in the control of sensorimotor tasks, also contributes to higher cognitive functions including reward, emotion and social interaction. The regulation of these behaviors has been largely ascribed to the monoaminergic system in limbic regions.However, the contribution of cerebellar dopamine signaling in the modulation of these functions remains largely unknown due to the lack of precise characterization of cerebellar dopaminoceptive neurons. By combining cell type-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 83 publications
(83 reference statements)
1
11
0
Order By: Relevance
“…Additional neuromodulators, such as dopamine and norepinephrine, are known to regulate cerebellar local circuitry. The cerebellar dopaminergic system has been shown to regulate reward-related information processing (Carta et al, 2019;Cutando et al, 2022). On the other hand, a role for norepinephrine has been established in cerebellar eyeblink conditioning (Gould, 1998;Cartford et al, 2004).…”
Section: Other Neuromodulatorsmentioning
confidence: 99%
“…Additional neuromodulators, such as dopamine and norepinephrine, are known to regulate cerebellar local circuitry. The cerebellar dopaminergic system has been shown to regulate reward-related information processing (Carta et al, 2019;Cutando et al, 2022). On the other hand, a role for norepinephrine has been established in cerebellar eyeblink conditioning (Gould, 1998;Cartford et al, 2004).…”
Section: Other Neuromodulatorsmentioning
confidence: 99%
“…Additionally, the olfactory bulb is a neural structure involved in olfaction [ 83 ]. In these structures, Ca 2+ rises in response to major neurotransmitters, such as γ-aminobutyric acid and dopamine [ 84 ]. Particularly in the cerebellum, the expression of dopamine receptors and eCS is common in Purkinje cells [ 81 , 85 ], and it is conceivable that eCS participates in Ca 2+ increase in response to dopamine as a Ca 2+ inducer.…”
Section: Ca 2+ Signaling and Mitochondriamentioning
confidence: 99%
“…This has been reported in survivors of other cancers; however, the CMS group seemed to face more difficulty in dealing with social relations (Barrera et al, 2005;Ness and Gurney, 2007;Lund et al, 2011). The cerebellum has been shown to participate in social functions (Cutando et al, 2022). Changes in dopamine D2 receptors levels in cerebellum of male mice during adulthood alter sociability and preference for social novelty (Cutando et al, 2022).…”
Section: Discussionmentioning
confidence: 83%
“…The cerebellum has been shown to participate in social functions (Cutando et al, 2022). Changes in dopamine D2 receptors levels in cerebellum of male mice during adulthood alter sociability and preference for social novelty (Cutando et al, 2022). Functional MRI studies have revealed three distinct representations for social function in cerebellum.…”
Section: Discussionmentioning
confidence: 99%